Update of the biochemical and molecular results of Portuguese patients with Familial Combined Hyperlipidaemia - Santos, T. (2012)
FCHL is a complex disorder with a highly atherogenic profile. The aim of this study is the biochemical/molecular characterization of FCHL patients. Molecular study of LPL, APOAIV, APOAV, APOCIII and USF1 (s1,s2) was performed in 35 index patients by PCR amplification and sequencing. Total cholesterol (TC), HDL-c, sdLDL, triglycerides (TG), apoB and apoCIII were measured in automated analysers. sdLDL was also analysed by electrophoresis with Lipoprint®. ApoAIV and ApoAV were measured by ELISA. For all patients, biochemical characterization of apolipoproteins and sdLDL before treatment was not possible to determine. Prior to medication the levels of TC (305±62mg/dL) and TG (380±269mg/dL) were high but HDL-c was normal (44±11mg/dL). Even under medication these patients presented high levels of CT (205±58mg/dL), TG (233±109mg/dL) and ApoCIII (15±4mg/dL) and normal levels of HDL-c (44±9mg/dL). ApoAIV (17±10mg/dL), ApoAV (156±140ng/mL) and ApoB (89±41mg/dL) levels were within normal range in majority of cases. Lipoprint® analysis of 8 patients under medication revealed an atherogenic pattern. Two new alterations were found. One patient with TC=271mg/dl and TG=275mg/dL carried APOAIV Q359_E362 (values without medication). Another patient with TC=419mg/dL and TG=1095mg/dL presented APOAV D332fsX336 and, even under medication, had high sdLDL (39 mg/dL, cut-off value 35mg/dl) and an atherogenic pattern with Lipoprint® analysis (pattern B). Some patients had a novel alteration APOCIII 3269C>A that was proven later that was a polymorphism. Patients with FCHL have increased cardiovascular risk that can be prevented with an early genetic identification and an extensive biochemical characterization that can be important to evaluate the efficacy of treatment.